Prediction of the wave induced by a gaint accumulation impoundment instability in Lantsang River - Daru HU; Shuyu WU; Chaopeng LUO; Hui DENG; Pengfei LI; Zhaoying WANG (地质科技通报)
Objective The RM hydropower station is proposed to be constructed in the upper reaches of the Lancang River. Its impoundment and operation might result in deformation and instability of the RS giant accumulation on the left bank near the dam, thereby triggering landslide-induced wave disasters and endangering the safety of the key hydraulic structures and the downstream residents. Methods This study combines extensive geological surveys and physical mechanics experiments to investigate the potential instability and failure modes of RS accumulation under reservoir filling. On this basis, a three-dimensional numerical model of the entire river channel from the RS accumlation to the dam section was established. An analysis of the dynamic evolution of landslide-wave chain disasters caused by RS accumulation was conducted, and parameters such as the initial wave height, wave height along the opposite bank, propagation characteristics, wave height at the dam front, and wave height climbing along the dam were predicted. Results The results indicate that as the reservoir water level is gradually elevated to an altitude of 2 800 meters, the RS accumulation is most likely to undergo a large-scale instability failure. The rear tensile fracture boundary is the crushed stone and soil layer of the accumulation within a certain range above the reservoir water level, and the front shear boundary is the fine-grained layer in the middle and lower parts of the accumulation. After the instability failure of the accumulation, it induces a landslide-induced wave. The height of the first wave peaks near the water entry point, approximately 31.5 meters, and lasts for about 15 seconds. As the wave propagates downstream, the wave height decreases by 39.5% at the No. 1 river bay, reaching the dam in approximately 147 s and continuing to climb along the dam slope. The climbing wave height is approximately 2.6 m and lasts for 180 s, with no risk of overtopping by the initial or subsequent smaller waves. After being impeded by the dam, the initial wave propagates upstream, creating a backflow phenomenon, which, combined with subsequent waves, forms a locally high wave area. At monitoring point P5, the maximum backflow wave height reaches approximately 4.56 m and lasts for 219 s. Conclusion During the wave propagation process, the topography of the river bay and backflow phenomena significantly accelerate the energy dissipation of the waves, effectively reducing the risk of wave impact and secondary disasters.